Efficacy and Tolerability of Anthracycline-Based Therapy in Elderly Patients With Diffuse Large B-Cell Lymphoma - Davis, Christine C. (Clin Lymphoma Myeloma Leuk, 2014)
We examined treatment with or without anthracyclines in 72 eldery diffuse large B-cell lymphoma patients (age ≥ 65 years) in a retrospective cohort analysis. Factors leading to treatment without an anthracycline included age and ejection fraction, whereas markers of tolerability were similar between groups. This study highlights the details of anthracycline tolerability in elderly lymphoma patients. INTRODUCTION: Although diffuse large B-cell lymphoma (DLBCL) can be cured with rituximab and anthracycline-based therapy, within the elderly population there are additional factors to consider in selecting a treatment regimen including comorbid conditions, decreased drug metabolism, decreased hematologic reserve, reduced performance status, and regimen-related toxicity. PATIENTS AND METHODS: We performed a retrospective cohort analysis of patients with DLBCL aged ≥ 65 years at time of diagnosis treated with either an anthracycline-containing regimen (ACR; n = 59) or a non-ACR (n = 13) to assess factors that led to treatment selection, tolerability, and outcomes. RESULTS: The mean age was 73 years in the ACR and 77 years in the non-ACR group (P = .009), and median left ventricular ejection fraction (LVEF) at diagnosis was 60% in the ACR group and 45% in the non-ACR group (P < .001). With an ACR, elderly DLBCL patients had a median overall survival of 28 months and a 2-year progression-free survival (PFS) of 64%. After an ACR, 14 patients [24%] (out of 59 total patients) had a decrease in LVEF, 7 patients [15%] (% is based off of those who we had the data collected, so this is out of 45 with this specific data) required a dose reduction of the anthracycline, and 15 patients [33%] (% is based off of those who we had the data collected, so this is out of 45 with this specific data) could not complete the regimen as planned. Hospitalization due to toxicity occurred in 20 patients [44%] (% is based off of those who we had the data collected, so this is out of 45 with data) of patients in the ACR group and 3 patients [75%] (% is based off of those who we had the data collected, so this is out of 4 with this specific data) in the non-ACR group, and was the only predictor of overall survival. CONCLUSION: Results of this study suggest that elderly patients with DLBCL experience meaningful PFS with ACRs, but a third experience toxicity requiring therapy modification. Future studies should examine larger patient populations and define treatments with outcomes similar to ACR that also decrease toxicity and hospitalization in the elderly DLBCL population.